Risk and control of food-related invasive diseases caused by group B Streptococcus sequence type 283 from cultured freshwater fish - ZHANG Xinhao; LIU Lisha; LI Hui; LI Bingyan; BAI Li (Zhongguo shipin weisheng zazhi, 2023)
Group B Streptococcus （GBS） is an important opportunistic pathogen that exists in a variety of animals and can infect humans， mainly causing a variety of invasive diseases in pregnant women and newborns. ST283 is a sequence type of GBS that has been found from freshwater fish cultured in Southeast Asia in recent years， and has attracted widespread attention because this type of GBS is suggested to cause food-related invasive diseases in human. As a major country in freshwater fish farming and consumption， China still needs to pay attention although no relevant cases have been reported in the inland. This paper elaborates on the available information on GBS ST283 in various countries to provide reference for the development of GBS monitoring and evaluation criteria in China.